Происхождение удмуртского народа: [монография] / М. Г. Атаманов-Эграпи - Атаманов-Эграпи Михаил Гаврилович (Удмуртия, 2010)
Экземпляры: КО (2011) / Инвентарный номер: 47616 / Цена: / Авт.знак: А 92 / ББК: 63.521(=664)